(untitled) - Linde, Leandri

Working towards SDG Target 12.3 baseline values: quantifying food losses in the fruit processing stage of the food supply chain in South Africa (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScFoodSc)--Stellenbosch University, 2023.